2008
DOI: 10.1093/rheumatology/kep034
|View full text |Cite
|
Sign up to set email alerts
|

Expression of endothelial protein C receptor in cortical peritubular capillaries associates with a poor clinical response in lupus nephritis

Abstract: Increased mEPCR expression in PTCs may represent a novel marker of poor response to therapy for LN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…Unexpectedly, mEPCR was found to be upregulated in the renal peritubular capillaries of patients with lupus nephritis compared with peritubular capillaries from normal kidneys (54). Those patients whose biopsies showed that more than 25% of the cortical peritubular capillaries expressed mEPCR responded poorly to therapy at 6 and 12 mo and tended to develop CKD (54). Interestingly, mEPCR as a biomarker of response to treatment was independent of biopsy class, activity and chronicity indices, GFR, and tubulointerstitial damage (54).…”
Section: Membrane Endothelial Protein C Receptormentioning
confidence: 97%
See 2 more Smart Citations
“…Unexpectedly, mEPCR was found to be upregulated in the renal peritubular capillaries of patients with lupus nephritis compared with peritubular capillaries from normal kidneys (54). Those patients whose biopsies showed that more than 25% of the cortical peritubular capillaries expressed mEPCR responded poorly to therapy at 6 and 12 mo and tended to develop CKD (54). Interestingly, mEPCR as a biomarker of response to treatment was independent of biopsy class, activity and chronicity indices, GFR, and tubulointerstitial damage (54).…”
Section: Membrane Endothelial Protein C Receptormentioning
confidence: 97%
“…The receptor may be shed in patients with active lupus (53). Unexpectedly, mEPCR was found to be upregulated in the renal peritubular capillaries of patients with lupus nephritis compared with peritubular capillaries from normal kidneys (54). Those patients whose biopsies showed that more than 25% of the cortical peritubular capillaries expressed mEPCR responded poorly to therapy at 6 and 12 mo and tended to develop CKD (54).…”
Section: Membrane Endothelial Protein C Receptormentioning
confidence: 97%
See 1 more Smart Citation
“…Although there have been intense efforts to identify biomarkers in serum and urine from LN patients, these have not yet yielded sufficiently robust markers to replace the renal biopsy. Previous studies have shown that endothelial changes such as increased protein levels of membrane protein C receptor (encoded by PROCR) in patients with LN predicts poor responses to therapy (9). Furthermore, increased levels were noted in biopsies of nonlesional, non-sun-exposed skin of LN patients, suggesting that alterations in the microvasculature are widespread and extend to the dermal vasculature (9).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that endothelial changes such as increased protein levels of membrane protein C receptor (encoded by PROCR) in patients with LN predicts poor responses to therapy (9). Furthermore, increased levels were noted in biopsies of nonlesional, non-sun-exposed skin of LN patients, suggesting that alterations in the microvasculature are widespread and extend to the dermal vasculature (9). Thus, analysis of this more readily accessible tissue, even distant from the primary affected organ, may provide an opportunity to explore surrogates for renal tissue analyses (10).…”
Section: Introductionmentioning
confidence: 99%